Internet Video Sharing as a Public Engagement Tool on Renewable Energy. (August 2015) - Biddinika, Muhammad Kunta; Indrawan, Bayu; Nakhshiniev, Bakhtiyor; Tokimatsu, Koji; Yoshikawa, Kunio; Takahashi, Fumitake
Abstract: Internet technology has made creating and sharing media content, including in audio and video format, easier and more accessible for public. Renewable energy technology has been utilizing internet video sharing technology for two main purposes. First, it is a promotional tool to disseminate information about the technology; second, internet becomes a tool for contemporary society to engage on renewable energy issues. This paper shows the importance beside the potential of internet video sharing to improve public engagement on renewable energy. The study shows how an internet video sharing, particularly featured by YouTube, may be an effective tool for renewable energy technology to engage with public.